Experimental and Monte Carlo absolute characterization of a medical electron beam using a magnetic spectrometer. (March 2016) - Gobet, F.; Caron, J.; Bessieres, I.; Bonnet, T.; Aléonard, M.M.; Antoine, M.; Barberet, P.; Comet, M.; Denis-Petit, D.; Feugeas, J.L.; Hannachi, F.; Hulin, S.; et al.
Abstract: The knowledge of the absolute energy distributions of the particles emitted from a clinical accelerator is important for the evaluation of Monte Carlo simulations developed for treatment planning. In this paper, an original approach is presented which allows to measure the absolute energy distribution of the electron beam delivered by a Varian 21Ex medical accelerator. The electron beam was characterized at the isocenter with calibrated image plates covering the exit window of a magnetic spectrometer. The characteristics of the electron beam emitted from an effective source have been inferred from the measurements using the Geant4 Monte Carlo code. The contribution of direct electrons to the absolute depth-dose curve in a water phantom is estimated. Highlights: We report on the characterization of the electron beam from a Varian 21Ex accelerator. The direct electrons' energy distribution at 9 MeV was measured in the isocenter. A magnetic spectrometer and image plates were used for absolute measurements. Water depth dose curve measurements and Monte Carlo simulations are confronted. The dose contribution at zmax due to direct electrons is estimated about 55–60%.